2022
DOI: 10.3389/fimmu.2022.794175
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tumor-Infiltrating Lymphocytes in Breast Cancer: A Proposal for Combining Immunohistochemistry and Gene Expression Analysis to Refine Scoring

Abstract: Scoring of tumor-infiltrating lymphocytes (TILs) in breast cancer specimens has gained increasing attention, as TILs have prognostic and predictive value in HER2+ and triple-negative breast cancer. We evaluated the intra- and interrater variability when scoring TILs by visual inspection of hematoxylin and eosin-stained tissue sections. We further addressed whether immunohistochemical staining of these sections for immune cell surface markers CD45, CD3, CD4, and CD8 and combination with nanoString nCounter® gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…In addition, many studies have reported that an intense TILs infiltration is associated with progression of disease [5,48,49]. Increasing levels of TILs have been associated with improved therapy outcome in HER2+ breast cancer and/or triple negative breast cancer patients [57]. Furthermore, we observed highly similar distribution pattern of CD56 + cells in the core tissue sample of healthy donor and breast cancer subtypes (Figure 2A).…”
Section: Our Results Clearly Indicate Significantly Decreased Express...supporting
confidence: 67%
“…In addition, many studies have reported that an intense TILs infiltration is associated with progression of disease [5,48,49]. Increasing levels of TILs have been associated with improved therapy outcome in HER2+ breast cancer and/or triple negative breast cancer patients [57]. Furthermore, we observed highly similar distribution pattern of CD56 + cells in the core tissue sample of healthy donor and breast cancer subtypes (Figure 2A).…”
Section: Our Results Clearly Indicate Significantly Decreased Express...supporting
confidence: 67%
“…Immune infiltration has been noted as a characteristic of gcGBM (53,66,67). As the prognostic role of CD3 and CD8 have yet to be established in gcGBM, there are numerous reports associating infiltrating lymphocytes with improved prognosis for several cancers (68)(69)(70)(71). In our analysis, both CD3 and CD8 proteins were expressed at least two-fold higher in several CD45-enriched AOIs of gcGBM compared to the same type of AOI in GBM samples (Fig.…”
Section: Glioblastoma Study Using Spatial Proteogenomic Assaymentioning
confidence: 54%
“…In the case of BC, immune cells invade the cancer tissue, and infiltrating lymphocytes play a central in cancer growth, so that the percentage of TILs is currently accepted as a useful prognostic factor for managing breast cancer patients. Histological methods (hematoxylin–eosin or immunohistochemistry staining) are used to evaluate the TILs percentage in paraffin-embedded BC tissue sections [ 28 , 32 ]. Although the assessment is specific to the tumor region, it does not consider the different subpopulations infiltrating the tumor, unless time-consuming and rather complex analyses are made (i.e., IHC with specific markers for each subpopulation).…”
Section: Discussionmentioning
confidence: 99%